MINI-REVIEW OF THYROID HORMONE: THE MASK BEHIND CARDIOVASCULAR DISEASES - Ramadhan M; Rohman F; Rozali N.A; Rumkabu Y.L.H; Rafsanjani F (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Cardiovascular disease (CVD) is the leading cause of mortality globally. Extensive attempts have been made to minimize and reduce the number of deaths, but the expected outcomes have not yet been achieved. It indicated that CVD had multiple etiologies. Several investigations have demonstrated an association between thyroid hormone and cardiovascular disease. In this review, we will describe the role of thyroid hormone in cardiovascular disease, both as a risk factor and a trigger for cardiovascular diseases such as heart failure and coronary heart disease. Also, the implications of thyroid hormone replacement therapy for improving cardiovascular disease.